The Effect of Working Capital Turnover and Fixed Asset Turnover on net Profit Margin in Manufacturing Companies of the Pharmaceutical Sub-Sector Listed on the Indonesia Stok Exchange for Period 2019-2023 - Marpaung, Deni Tamora; Mulyani, Sri; Puspita, Bella (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
This study aims to analyze the effect of working capital turnover and fixed asset turnover on Net Profit Margin (NPM) in pharmaceutical manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2019–2023. The research employs a quantitative approach using descriptive methods, with secondary data from annual financial reports as the primary source. The sample consists of seven companies selected through purposive sampling criteria. The analysis method used is multiple linear regression with the t-test to measure partial effects, the F-test for simultaneous effects, and the coefficient of determination (R²) to assess the contribution of independent variables to the dependent variable. The results show that working capital turnover significantly influences Net Profit Margin, while fixed asset turnover does not show a significant impact. Simultaneously, both independent variables affect NPM, with a moderate level of contribution. This study contributes to better management of working capital and fixed assets to improve company profitability. The findings are expected to serve as a reference for academics and practitioners in developing financial strategies in Indonesia's pharmaceutical sector.